Pathogenicity of Fungi Associated with the Wheat Crown Rot Complex in Oregon and Washington - Smiley, Richard W (Plant disease, 2005)
Crown rot of wheat in the Pacific Northwest is caused by a complex including Bipolaris sorokiniana, Fusarium avenaceum, F. culmorum, F. pseudograminearum, and Microdochium nivale. Relative pathogenicity was examined under greenhouse conditions for 178 isolates of the five species, and under field conditions for 24 isolates of B. sorokiniana, F. culmorum, and F. pseudograminearum. In the greenhouse, all five species reduced (P < 0.05) plant height relative to noninoculated controls. Disease severity was inversely correlated with plant height for the three Fusarium spp. In one or more of four experiments with spring wheat in the field, all three species reduced stand establishment and density of mature heads and increased the incidence and severity of crown rot. F. culmorum and F. pseudograminearum caused the greatest disease severity and plant damage and were the only pathogens that reduced grain yield. Virulence ratings were variable among isolates for each species in all greenhouse and field experiments. Isolate variability was especially high for the location and year variables in field experiments. Mixtures of multiple isolates are required for future research